Moisture monitoring in clay embankments using electrical resistivity tomography. (1st September 2015) - Gunn, D.A.; Chambers, J.E.; Uhlemann, S.; Wilkinson, P.B.; Meldrum, P.I.; Dijkstra, T.A.; Haslam, E.; Kirkham, M.; Wragg, J.; Holyoake, S.; Hughes, P.N.; Hen-Jones, R.; et al.
Highlights: New remote monitoring technologies/approaches. Proactive maintenance using subsurface images. Increased time for early interventions. Abstract: Systems and methods are described for monitoring temporal and spatial moisture content changes in clay embankments using electrical resistivity tomography (ERT) imaging. The methodology is based upon development of a robust relationship between fill resistivity and moisture content and its use in the transformation of resistivity image differences in terms of relative moisture content changes. Moisture level and moisture content movement applications are exemplified using two case histories from the UK. The first is the BIONICS embankment, near Newcastle (NE England), which was constructed in 2005 using varying degrees of compaction of a medium plasticity sandy, silty clay derived from the Durham Till. The second is a Victorian embankment south of Nottingham (Central England), constructed in 1897 using end tipping of Late Triassic siltstone and mudstone taken from local cuttings. Climate change forecasts for the UK suggest that transportation earthworks will be subjected to more sustained, higher temperatures and increased intensity of rainfall. Within the context of preventative geotechnical asset maintenance, ERT imaging can provide a monitoring framework to manage moisture movement and identify failure trigger conditions within embankments, thus supporting on demand inspection scheduling and low cost early interventions.